Early impact of COVID-19 social distancing on social determinants of health and their effects on mental health and quality of life of Korean undergraduate students - Lee, Kyeongeun; Han, Sola; Suh, Hae Sun (Frontiers in Public Health, 2023)
Introduction: This study aimed to investigate the association between social determinants of health and perception of COVID-19 social distancing/mental health/quality of life during COVID-19 social distancing in Korean undergraduate students using online survey data augmented with natural language processing. Methods: An online cross-sectional survey including sociodemographic characteristics, students’ perceptions of COVID-19 social distancing, and social determinants of health was conducted between July and November in 2020. We conducted logistic regression analysis to investigate the relationship between social determinants of health (independent variables) and perceptions of COVID-19 social distancing, mental health, and quality of life (dependent variables). This association was augmented using sentiment analysis and word clouds by visualizing open-ended comments on COVID-19 social-distancing policies. Results: Data were collected from 1,276 undergraduate students. Participants who experienced negative impacts on their social-networking activities due to COVID-19 social distancing were at significantly higher odds to perceive COVID-19 social distancing as not being beneficial (odds ratio [OR] = 1.948, 95% confidence interval [CI] 1.254–3.027), to have increased stress levels (OR = 1.619, 95% CI 1.051–2.496), and to experience decreased quality of life over five weeks (OR = 2.230, 95% CI 1.448–3.434) against those who answered neutrally. In contrast, Participants who reported positive perceptions of social-networking activities during the COVID-19 pandemic had lower odds of feeling depressed or anxious (OR = 0.498, 95% CI 0.278–0.894) and reporting a low quality of life over five weeks (OR = 0.461, 95% CI 0.252-0.842) compared to those who reported neutral perceptions. Furthermore, the results of the word cloud and sentiment analyses showed that most students perceived social distancing negatively. Conclusions: The government’s social-distancing policy to prevent the spread of COVID-19 may have had a negative impact, particularly on undergraduate students' social-networking activities. This highlights the need for greater social support for this population, including access to psychotherapeutic resources, and improvements in policies to prevent infectious diseases while still maintaining social connections.